Purinergic receptors P2RX4 and P2RX7 in familial multiple sclerosis. Issue 6 (13th April 2017) - Sadovnick, A Dessa; Gu, Ben J; Traboulsee, Anthony L; Bernales, Cecily Q; Encarnacion, Mary; Yee, Irene M; Criscuoli, Maria G; Huang, Xin; Ou, Amber; Milligan, Carol J; Petrou, Steven; Wiley, James S; et al.
Abstract : Exome sequencing analysis in a Canadian family with high incidence of multiple sclerosis has led to the identification of pathogenic mutations in the P2RX7‐P2RX4 locus. The identified mutations were shown to impair surface expression of these purinergic receptors, and nominates the disruption of transmembrane cation channels and impairment of phagocytosis as the pathological mechanism responsible for the onset of multiple sclerosis in this family. Abstract: Genetic variants in the purinergic receptors P2RX4 and P2RX7 have been shown to affect susceptibility to multiple sclerosis (MS). In this study, we set out to evaluate whether rare coding variants of major effect could also be identified in these purinergic receptors. Sequencing analysis of P2RX4 and P2RX7 in 193 MS patients and 100 controls led to the identification of a rare three variant haplotype ( P2RX7 rs140915863:C>T [p.T205M], P2RX7 rs201921967:A>G [p.N361S], and P2RX4 rs765866317:G>A [p.G135S]) segregating with disease in a multi‐incident family with six family members diagnosed with MS (logarithm of odds = 3.07). Functional analysis of this haplotype in HEK293 cells revealed impaired P2X7 surface expression ( P < 0.01), resulting in over 95% inhibition of adenosine triphosphate (ATP)‐induced pore function ( P < 0.001) and a marked reduction in phagocytic ability ( P < 0.05). In addition, transfected cells showed 40% increased peak ATP‐induced inward current ( P < 0.01), and a greater Ca 2+ response to the P2X4 135S variant compared with wild type ( P < 0.0001). Our study nominates rare genetic variants in P2RX4 and P2RX7 as major genetic contributors to disease, further supporting a role for these purinergic receptors in MS and the disruption of transmembrane cation channels leading to impairment of phagocytosis as the pathological mechanisms of disease.